The Profile of Soft Tissue Sarcoma Patients who Undergo Radiotherapy in Dr. Hasan Sadikin General Hospital Bandung - Antony Abel Adibrata; Marhendra Satria Utama; Adji Kusumadjati (Indonesian Journal of Cancer, 2022)
Background: Soft Tissue Sarcoma is one of the rare cancers that increased in number in the last few years, but information about soft tissue sarcoma patients was still limited, especially in West Java, Indonesia. This study aimed to find out the patient profile and the histopathological cell distribution of soft tissue sarcoma patients who undergo radiotherapy. Methods: The study design was retrospective descriptive quantitative with the total sampling method. This study was done by observing all patients’ medical records registered from January 1, 2018, until December 31, 2019, in the Hospital-Based Cancer Registry of Radiology Department of Dr. Hasan Sadikin General Hospital Bandung, with the inclusion criterion of patients diagnosed with soft tissue sarcoma.  Results: A total of 5% (n = 75) from 1,388 cases registered were soft tissue sarcoma. The most common patient profile was female (57.3%) and age group 45–54 years (21.3%). The chief complaint was dominated by a painless mass (56.0%) at the lower limb (37.8%) with the most frequent cell of fibrosarcoma (17.3%), the most intention of the radiotherapy of curative adjuvant (78.7%). Conclusions: The number of soft tissue sarcoma is small compared to other malignancies. It is more common in women, the most age group is from 45 to 54 years with the median of 47 years old, ranging from 9 to 90 years, it tends to occur in the lower limb with a chief complaint of a painless mass, and the most frequent cell is fibrosarcoma. The common treatment combination is surgery with radiotherapy